El pensamiento dibujado como parte de los procesos de ideación y creación de las formas en la arquitectura latinoamericana contemporánea - Ceaglio, Carolina Ester (2018)
The forms are symbolically constructed, and their possibilities are limited by their place and time. Today´s architectural forms scenario presents different responses, different project processes and positions in the way of understanding architecture. This article is part of a research work that tries to revise these different positions, particulary focused on a group of Latin American architects whose work presents special characteristics that make them important in the current architecture scene.